PERSEPSI WISATAWAN TERHADAP CITRA DAYA TARIK WISATA MONUMEN PERJUANGAN RAKYAT BALI DI KOTA DENPASAR (Jurnal Destinasi Pariwisata, 2026)
The Study aims Balinese People's Struggle Monument is a tourist destination capable of providing cultural and historical experiences for tourists. It also boasts adequate tourism product components, including attractions, accessibility, amenities, and amenities. This, in turn, fosters a positive perception of the Balinese People's Struggle Monument's appeal. Regarding tourist perceptions of the Balinese People's Struggle Monument's appeal, a questionnaire was used, with 58 respondents as the sample. The analysis, conducted through validity testing of cognitive image, unique image, and affective image indicators, confirmed the data was valid and suitable for use as a research instrument. Furthermore, reliability testing also confirmed its suitability as a research instrument.The characteristics of the respondents, based on the questionnaire data, were analyzed based on the origin of the tourists, with the predominance of domestic tourists; gender, with female tourists; age, with tourists aged 16-25 years old, the largest number of visitors; occupational background, with students predominating; educational level, with undergraduate tourists predominating; and frequency of visits, with previous visitors predominating. The results of the study of tourists' perceptions of the image of the tourist attraction of the Balinese people's struggle monument based on the results of data processing from the questionnaire, namely from the indicators of cognitive image, unique image, and affective image, have an average score in the agree category, so that in this case the tourist attraction of the Balinese people's struggle monument from the perception of tourists can be said to have a positive image for tourists.